Stability Study of Tadaflexe (Tadalafil 10 mg) Oral Gel Sachet in Yemeni Honey - Kadi, Hussien O; AL-Maktari, Alaa (Global Journal of Medical and Clinical Case Reports, 2025)
Introduction: Tadalafil is a selective phosphodiesterase type 5 (PDE5) inhibitor widely used for the treatment of erectile dysfunction and other related disorders. Oral gel formulations are gaining interest due to improved patient compliance, faster onset of action, and ease of administration. This study evaluates the stability of an oral tadalafil gel formulation stored under both long-term and accelerated conditions over six months. Methods: The stability of Tadaflexe, a novel oral gel sachet formulation containing tadalafil (10 mg per 5 g Yemeni honey base), was evaluated under accelerated and predicted long-term conditions according to ICH Q1A(R2) guidelines. Physical appearance, pH, drug assay, viscosity, and microbial safety were assessed over six months at 40 °C ± 2 °C / 75% RH ± 5%. Results: Demonstrated that oral Tadaflexe (tadalafil 10 mg) gel maintained acceptable pharmaceutical quality, with no significant changes in appearance, drug assay (>95% retention), or microbial contamination. Yemeni honey proved to be an effective natural excipient for stability, offering viscosity and antimicrobial properties. Conclusion: The oral Tadaflexe (tadalafil 10 mg) gel demonstrated excellent stability across all tested parameters over six months. These findings provide a strong basis for further clinical development and market readiness of the product.